Free energy of bare and capped gold nanoparticles permeating through a lipid bilayer - Mhashal, Anil R.; Roy, Sudip (Chemphyschem, 2016)
Herein, we study the permeation free energy of bare and octane-thiol-capped gold nanoparticles (AuNPs) translocating through a lipid membrane. To investigate this, we have pulled the bare and capped AuNPs from bulk water to the membrane interior and estimated the free energy cost. The adsorption of the bare AuNP on the bilayer surface is energetically favorable but further loading inside it requires energy. However, the estimated free-energy barrier for loading the capped AuNP into the lipid membrane is much higher compared to bare AuNP. We also demonstrate the details of the permeation process of bare and capped AuNPs. Bare AuNP induces the curvature in the lipid membrane whereas capped AuNP creates an opening in the interacting monolayer and get inserted into the membrane. The insertion of capped AuNP induces a partial unzipping of the lipid bilayer, which results in the ordering of the local lipids interacting with the nanoparticle. However, bare AuNP disrupts the lipid membrane by pushing the lipid molecules inside the membrane. We also analyze pore formation due to the insertion of capped AuNP into the membrane, which results in water molecules penetrating the hydrophobic region.